Exploring the usage of visual effect in advertisement for awareness campaigns - Mazlan, Aniq Anas; Mohd Lazim, Nur Aniza; Che Din, Sharkawi (Universiti Teknologi MARA, Perak, 2025)
This study exploring the use of visual effects (VFX) in awareness campaign advertisements through a content analysis approach. In today’s visually driven media environment, awareness campaigns increasingly rely on visual storytelling to convey critical messages effectively. On the other hand, nothing is known about the design and use of VFX elements in these advertisements, including narrative structure, green screen, compositing, colour grading, and typography. The objective of this study is to examine how these five elements of VFX are applied across different campaigns to construct meaning, emphasize key themes, and support emotional tone. This research uses qualitative content analysis as its methodological framework, focusing on ten selected awareness campaign videos. Each video was analysed through word cloud generation, which helped visually identify and interpret frequently occurring terms associated with each VFX element. The findings reveal that narrative structure, colour grading, and typography were consistently rated higher across the campaigns, suggesting that these elements are central to visual clarity and message reinforcement. In contrast, green screen and compositing were used more selectively, particularly in campaigns with more realistic or documentary-style approaches. The study concludes that while all five VFX elements contribute to the construction of visual meaning, those related to emotional tone and storytelling are more consistently integrated in awareness campaigns.